Multi-wavelength global maps of Jupiter and Saturn using Cassini imaging system data - Xinyue Wang; Liming Li; Xun Jiang; Robert A. West (Scientific Data)
Abstract The Imaging Science Subsystem onboard the Cassini spacecraft recorded numerous high-quality images of Jupiter and Saturn at various wavelengths, from ultraviolet to near-infrared, during its 20-year mission from 1997 to 2017. Using these images, we have developed global maps of Jupiter and Saturn across multiple wavelengths. These maps reveal the global atmospheric structures of Jupiter and Saturn, offering a comprehensive tool to study the physical and dynamic processes of these atmospheric systems on a global scale. Additionally, these multi-wavelength maps, which probe different pressure levels within the atmospheres, help to explore the vertical structure of these processes. Moreover, global maps at different times enable tracking the movement of dynamic phenomena (e.g., clouds, storms, vortices, eddies, waves, and turbulence), thereby enhancing our understanding of atmospheric dynamics on the giant planets.